The Effects of Inhaling Lavender Fragrance on Stress and Anxiety during Sheath Take out in Patients after Coronary Angiography - Fatemeh Teymouri; Nahid Rajai; Zahra Farsi; Mohammad Pourmirzai (Institue of Medicinal Plants, ACECR, 2019)
Background: During the removal of the angiographic sheath, due to the patientchr('39')s vigilance and observation of the process, the patient experiences high levels of anxiety and stress. Objective: To determine the effects of inhalation of lavender essential oil on stress and anxiety during sheath take out in patients after coronary angiography. Method: In a semi-experimental study, 70 patients were selected by random sampling method in 2012 - 2013 and randomly assigned to two experimental and control groups. After leaving the shield (4 hours after the completion of the angiography), the Spielberger anxiety questionnaire was completed by the patients in both groups. After 70 minutes, the patients in the experimental group smelled two drops of lavender essential oil and the control group smelled placebo for 20 minutes. At the end of 20 minutes, the anxiety and stress levels of the patients assessed again and compared with pretest. Results: After intervention, anxiety (P = 0.001) and stress (P <0.001) in the experimental group were significantly lower than the control group. Also, the anxiety and stress of the experimental group in the post-intervention phase was significantly lower than before the intervention (P <0.001). Fisherchr('39')s exact test showed a significant difference between the two groups in terms of anxiety levels after intervention (P = 0.001); such that the majority of the experimental group showed a slight anxiety level (67.9%). Conclusion: The use of lavender essential oil during sheath take out in patients after coronary angiography can reduce stress and anxiety.